Delivering Benefits at Speed Through Real-World Repurposing of Off-Patent Drugs: The COVID-19 Pandemic as a Case in Point - Rogosnitzky, Moshe; Berkowitz, Esther; Jadad, Alejandro R (JMIR Publications, 2020)
Real-world drug repurposing-the immediate "off-label" prescribing of drugs to address urgent clinical needs-is a widely overlooked opportunity. Off-label prescribing (ie, for a nonapproved indication) is legal in most countries and tends to shift the burden of liability and cost to physicians and patients, respectively. Nevertheless, health crises may mean that real-world repurposing is the only realistic source for solutions. Optimal real-world repurposing requires a track record of safety, affordability, and access for drug candidates. Although thousands of such drugs are already available, there is no central repository of off-label uses to facilitate immediate identification and selection of potentially useful interventions during public health crises. Using the current coronavirus disease (COVID-19) pandemic as an example, we provide a glimpse of the extensive literature that supports the rationale behind six generic drugs, in four classes, all of which are affordable, supported by decades of safety data, and targeted toward the underlying pathophysiology that makes COVID-19 so deadly. This paper briefly summarizes why cimetidine or famotidine, dipyridamole, fenofibrate or bezafibrate, and sildenafil citrate are worth considering for patients with COVID-19. Clinical trials to assess efficacy are already underway for famotidine, dipyridamole, and sildenafil, and further trials of all these agents will be important in due course. These examples also reveal the unlimited opportunity to future-proof our health care systems by proactively mining, synthesizing, cataloging, and evaluating the off-label treatment opportunities of thousands of safe, well-established, and affordable generic drugs.